The Effectiveness of Summative Assessment in Work-Based Learning Practice - Mohabuth, Abdool Qaiyum (Journal of Education and Vocational Research, 2015)
Summative assessment aims at providing measurement of student’s understanding. It is argued that summative assessment is used for reporting and reviewing, besides providing an overall judgment of achievement. While summative assessment is a well defined process for learning that takes place in the classroom environment, its application within the Work-based Learning (WBL) practice environment is still being structured. This paper discusses the effectiveness of summative assessment in WBL practice from a mixed-method research study involving both quantitative and qualitative analysis. A survey questionnaire was designed for exploring the perceptions of mentors and students about summative assessment in WBL practice. The questionnaire was administered to the University of Mauritius students and mentors who supervised students for their WBL practice at the respective placement settings. Some students were also interviewed to capture their views and experiences about the application of summative assessment in WBL practice. Semi-structured interviews were also conducted with three experienced mentors who have assessed students on WBL practice. Findings reveal that most students had positive experiences about their summative assessments in WBL practice. They felt comfortable and confident to be assessed by their mentors in their placement settings and wished that the effort and time that they devoted to their learning be recognized and valued. Mentors also confirmed that summative assessment is a valid and reliable strategy in WBL practice, enabling them to better monitor and coach students to achieve the expected learning outcomes.